Using Visual Representations to Demonstrate Complexity in Mixed Emotional Development Across Childhood - Fotheringham, Francesca; Herman, Matthias; Robbins, Erin; Dritschel, Barbara (Frontiers in Psychology, 2021)
Previous studies have shown a developmental trend in mixed emotional understanding. As children develop throughout childhood, they begin to recognise simultaneity of positive and negative emotions. However, previous studies have limited ecological validity as they assessed emotion choice using only a single positive and single negative emotion. Therefore, the present study aims to broaden the understanding of mixed emotional development by allowing a wider emotion choice. Mixed emotions were measured using the Analogue Emotions Scale (AES) which allows both intensity of the emotional responses and time to be captured. In the present study 211 children aged 4-10 were divided into one of three protagonist conditions, (self, peer, and adult) and read a vignette about the protagonist moving house. Choosing from seven emotions (happy, calm, surprise, sad, worry, fear, anger) they plotted the intensity and duration of each emotion they thought was represented in the vignette. The present study replicated the developmental trend that younger children are more likely than older children to choose a single emotion, and older children are more likely to perceive more simultaneity of emotion than younger children. This trend was demonstrated in the number of emotions chosen, and also the complexity of the AES pattern plotted. Additionally, the present study extended previous research by demonstrating that by broadening the emotion choice, the emotion interaction is more complex than previous studies were able to show.